Prevention of Juvenile Delinquency through Collaboration between Mahallas and Educational Institutions - Tursunbaev Dilshod Tashkenbaevich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Juvenile delinquency is a significant social challenge that affects families, schools, and communities. This study examines the collaboration between mahallas and educational institutions in preventing youth involvement in criminal behavior. Through qualitative analysis, including interviews and observations, the research highlights how joint programs foster moral guidance, social responsibility, and constructive engagement among young people. Findings indicate that cooperation between community and school strengthens family support, promotes positive behavioral norms, and reduces the risk of delinquency. Culturally sensitive and sustainable strategies are essential to ensure long-term effectiveness.